Organization of selected Domingo Abella Collection of the National Historical Commission of the Philippines - Cruz, Roscelle C. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
The Domingo Abella Collection was donated by the family to the National Historical Commission of the Philippines with the intent and sincere desire to contribute to the enrichment of research and writing in the Philippine history and culture. For this project, records pertaining to Domingo Abella’s directorship of the National Archives of the Philippines (1967 – 1975) was processed. The collection underwent appraisal and selection, preventive conservation, rehousing and labeling, and creation of a user guide based on Describing Archives: A content Standard (DACS) for general description and file level inventory locating the exact folder and box numbers of the records.